1998
DOI: 10.1002/jmri.1880080605
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrafast half‐Fourier single‐shot turbo spin‐echo sequence with turbo spin‐echo sequences for T2‐weighted imaging of the female pelvis

Abstract: So that we might evaluate the ultrafast half-Fourier single-shot turbo spin-echo (HASTE) sequence in T2-weighted MRI of the female pelvis and compare it with the turbo spin-echo (TSE) sequence, we prospectively studied 60 consecutive females with suspected abnormalities of the pelvis. For all MR examinations, we used a 1.5-T superconductive magnet with a phased array coil. The HASTE sequence was applied with TR/effective TE/echo train = infinity/90/64 and a 128 x 256 matrix (acquisition time: .3 sec/slice), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…However, these sequences-such as single-shot FSE with half-Fourier acquisition and multi-shot echoplanar imaging-could not replace TSE sequencing because of their limited spatial resolution and low tissue contrast. [8][9][10] True FISP provides a higher signal-to-noise (S W N) ratio for the assessment of uterine anatomy deˆnition, as reported previously. 7 Therefore, it is natural that True FISP can be expected to function as an innovative and faster T2-weighted imaging method for evaluating ovarian pathology.…”
Section: Discussionmentioning
confidence: 77%
“…However, these sequences-such as single-shot FSE with half-Fourier acquisition and multi-shot echoplanar imaging-could not replace TSE sequencing because of their limited spatial resolution and low tissue contrast. [8][9][10] True FISP provides a higher signal-to-noise (S W N) ratio for the assessment of uterine anatomy deˆnition, as reported previously. 7 Therefore, it is natural that True FISP can be expected to function as an innovative and faster T2-weighted imaging method for evaluating ovarian pathology.…”
Section: Discussionmentioning
confidence: 77%
“…Studies have been conducted to compare 2D and 3D half-Fourier TSE sequences with standard 2D T2-weighted TSE sequences in MRI of the female pelvis. These studies [7][8][9] showed good image quality and improved time efficiency with the 2D half-Fourier TSE sequence and higher contrast, improved time efficiency, and superior through-plane resolution (2-3 mm) with the 3D half-Fourier TSE sequence. However, no attempt was made in those studies to generate multiplanar reconstructions of the 3D source data sets because the slice thickness of 2-3 mm seemed insufficient for acquisition of reformations of high quality.…”
Section: Discussionmentioning
confidence: 90%
“…The other method to speed T2‐weighted FSE imaging is to use a longer echo train length (5, 8). Single‐shot FSE with half‐Fourier acquisition, such as HASTE, has been introduced for the complement sequence in the evaluation of the female pelvis (19, 20).…”
Section: Discussionmentioning
confidence: 99%
“…Single‐shot FSE with half‐Fourier acquisition, such as HASTE, has been introduced for the complement sequence in the evaluation of the female pelvis (19, 20). This sequence is fast enough to freeze the peristalsis of the intestine and respiratory motion of the abdominal wall; thus, imaging free of motion‐artifacts can be obtained (8). However, in comparison to high‐resolution T2‐weighted FSE or turbo spin‐echo imaging, less spatial resolution and less lesion conspicuity are problems because the use of very long echo train length may cause blurring effects in single‐shot imaging, and may induce magnetization transfer effects that could reduce T2 contrast (3, 8, 21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation